Cyber Crime and Limiting Online Child Predation: A Comprehensive Examination - Johnson, Connor F (My University, 2024)
In today's digital world, technology has transformed how society functions and communicates. While these advancements make it easier for people to connect and access information, they also increase the risk of online child predation. The widespread use of the internet as a platform for socializing and sharing information has created an environment where illegal activities like cybercrime endanger vulnerable groups. To reduce the risks and consequences of these criminal acts, revisions to legislation and improved support for minors are essential. This paper examines the link between cybercrime and the pressing need to decrease online child predation.
Keywords: Cyber Crime, Child Exploitation, Legal Revisions